Patrones ecológicos y variación cíclica de la estructura trófica de las comunidades nectónicas en lagunas costeras del Pacífico de México - Yáñez-Arancibia, Alejandro (1978)
Trabajo presentado en el Simposio "Marine Sciences in the Americas" Interciencia Association, en Panel II "Ecology and Environmental Protection", San José, Costa Rica, 2 al 7 de julio, de 1977. Publicado con anterioridad en An. Centro Cienc. del Mar y Limnol. Univ. Nal. Autón. México, 5: 287-306, 1978. Contribución 82 del Centro de Ciencias del Mar y Limnología, UNAM. The coastal lagoons of the state of Guerrero (central Pacific coast of Mexico), present an environmental physiology cycle with three ecological annual periods: Period 1 (salinities from 15 to 34°/oo), from August to November, lagoons in contact with the sea through an open pass in the barrier bar, permitting a biological, physical and chemical exchange. Period 2 (salinities higher than 35°/oo), from November to May, lagoons isolated from the sea and evaporation exceeds freshwater input, there is a minimum volume of water inside the lagoons. Period 3 (salinities lower than 15°/oo), from May to August, lagoons isolated from the sea and freshwater input exceeds the rate of evaporation, there is a maximum volume of water inside the lagoons.